A study on the importance of the corporate reputation toward Sime Darby Bhd: perspective of employees in procurement department at Sime Darby Sdn Bhd Pasir Gudang / Nur Hamizah Ideres - Ideres, Nur Hamizah (2009)
The Importance of Corporate Reputation towards Sime Darby Group Sdn Bhd is conducted due to the problem statement which had been found by the researcher recently. The problem statement which stated that the acquisition of Institut Jantung Negara (IJN) is been asked by the Ministers either Sime Darby can maintain the good corporate reputation or not in order to balance it with the good service quality and also the social responsibility to the people. The research which is been conducted at Sime Darby Engineering Sdn Bhd Pasir Gudang has taken 56 employees from the Procurement Department as a sample. The findings shows that all the independent variables are significance with the dependent variable. The Independent Variable includes the element of marketing, branding, corporate communication, customer satisfaction and also the sponsorship. The most influence factors are the marketing and corporate communication. The researcher had concluded that Sime Darby Group Sdn Bhd should emphasize more on marketing effort and also the corporate communication seems it will contribute much to the good corporate reputation.